Analisis Pengaruh Price Earning Ratio Terhadap Return Saham Pada PT. Siantar Top TBK - Fani Fastabikul Hairat; Puji Muniarty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this research is to determine the effect of price earning ratio on stock returns at PT. Siantar Top Tbk. The population in this study were 12 financial reports at PT. Siantar Top TBK for the period 2012 - 2022. The research sample was taken using a non-probability sampling technique to obtain a sample of 12 years of financial reports. The results of this research indicate that the Price Earning Ratio has no significant effect on stock returns at PT. Siantar Top, TBK.